Fully depleted, back-illuminated charge-coupled devices fabricated on high-resistivity silicon. - Holland, S.E (IEEE Transactions on electron devices)
Charge-coupled devices (CCDs) have been fabricated on high-resistivity, n-type silicon. The resistivity, on the order of 10 000 Ω·cm, allows for depletion depths of several hundred micrometers. Fully depleted, back-illuminated operation is achieved by the application of a bias voltage to an ohmic contact on the wafer back side consisting of a thin in situ doped polycrystalline silicon layer capped by indium tin oxide and silicon dioxide. This thin contact allows for a good short-wavelength response, while the relatively large depleted thickness results in a good near-infrared response.